Mesoporous Silica Administration as a New Strategy in the Management of Warfarin Toxicity: An In-Vitro and In-Vivo Study - Fatemeh Farjadian; Fatemeh Parsi; Reza Heidari; Khatereh Zarkesh; Hamid Reza Mohammadi; Soliman Mohammadi-Samani; Lobat Tayebi (Advanced Pharmaceutical Bulletin)
Purpose: Warfarin is one of the most widely used anticoagulants that functions by inhibiting vitamin K epoxide reductase. Warfarin overdose, whether intentional or unintentional, can cause life-threatening bleeding. Here, we present a novel warfarin adsorbent based on mesoporous silica that could serve as an antidote to warfarin toxicity. Method: Amino-functionalized mesoporous silica (MS-NH2 ) was synthesized based on the co-condensation method through a soft template technique followed by template removal. The prepared structure and functional group were studied by Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) checked the morphology. The capacity of MS-NH2 in the adsorption of warfarin was evaluated in vitro, at pH=7.4 and pH=1.2. In vivo evaluations were performed in control and warfarin-overdosed animal models. Overdosed animals were treated with MS-NH2 by oral gavage. Biomarkers of organ injury were assessed in animal serum. Results: The MS-NH2 was relatively uniform, spherical with defined diameters (400 nm) and porous structure. Synthesized particles had a large surface area (1015 m2 g-1) and mean pore diameter of 2.4 nm which led to considerable adsorption capacity for warfarin 1666 mg/g. In vivo studies revealed that oral administration of MS-NH2 in mice poisoned with warfarin caused a significant difference (P<0.05) in the International Normalized Ratio (INR) and prothrombin time (PT). Moreover, the warfarin with MS-NH2 group demonstrated a notable decrease in biomarkers associated with tissue damage, such as bilirubin, lactate dehydrogenase (LDH), alanine aminotransferase (ALT), and aspartate aminotransferase (AST). Conclusion: The results confirm that MS-NH2 administration can be an effective treatment for warfarin toxicity and could potentially mitigate the adverse effects of warfarin poisoning.